A rare case of paraneoplastic neurological syndrome with ovarian teratoma - Kumar, Anita; Dabral, Anjali; Panwar, Megha; Bajaj, Bindu; Sanapala, Sukanya; Sharma, Deepti (International Journal of Research in Medical Sciences, 2022)
Paraneoplastic neurological syndrome (PNS) is a neuropathological disorder of central nervous system, in this the patient presents with a tumor anywhere in the body with diverse neuropsychiatric symptoms. The clinical manifestation of the tumor may be preceded by PNS. We are reporting a case of a 23-year-old married nulliparous female who came to the gynaecology outpatient department (OPD) with the history of mass per abdomen for the past four months and also undergoing treatment for acute psychosis, memory loss and cognitive impairment for the past five months. Her symptoms were not relieved on treatment. After clinical, laboratory and radiological evaluation possibility of paraneoplastic neurological syndrome associated with ovarian teratoma was made. Patient was taken up for staging laparotomy with U/L salpingoophrectomy. After surgical treatment her psychiatric symptoms rapidly improved and her psychiatric medications doses was reduced. PNS should be suspected in female patients presenting with an acute history of neuropsychiatric symptoms. Tumor resection should be performed at the earliest to improve patient outcomes.